2020
DOI: 10.3390/ijerph17176052
|View full text |Cite
|
Sign up to set email alerts
|

Can Air-Conditioning Systems Contribute to the Spread of SARS/MERS/COVID-19 Infection? Insights from a Rapid Review of the Literature

Abstract: The airborne transmission of SARS-CoV-2 is still debated. The aim of this rapid review is to evaluate the COVID-19 risk associated with the presence of air-conditioning systems. Original studies (both observational and experimental researches) written in English and with no limit on time, on the airborne transmission of SARS-CoV, MERS-CoV, and SARS-CoV-2 coronaviruses that were associated with outbreaks, were included. Searches were made on PubMed/MEDLINE, PubMed Central (PMC), Google Scholar databases, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 64 publications
1
120
0
6
Order By: Relevance
“…Social distancing (91) and well-fitting masks (121) help to reduce aerosol transmission as well as large droplet transmission, but other precautions specific to aerosols are also needed. These could include operational changes to ventilation systems in public buildings and public transport (98)(99)(100)(101), UV lamps in some indoor locations (112,116,117), and attention to wind (61) and sunlight (7) in outdoor settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social distancing (91) and well-fitting masks (121) help to reduce aerosol transmission as well as large droplet transmission, but other precautions specific to aerosols are also needed. These could include operational changes to ventilation systems in public buildings and public transport (98)(99)(100)(101), UV lamps in some indoor locations (112,116,117), and attention to wind (61) and sunlight (7) in outdoor settings.…”
Section: Discussionmentioning
confidence: 99%
“…The risk then depends on the duration of exposure (16) as well as the fresh air ventilation rate. Conversely, longdistance indoor transport by natural or mechanical ventilation is a potential hazard that does not exist for infection by larger droplets (23,97,98).…”
Section: Implications For Ventilationmentioning
confidence: 99%
“…Otherwise, it is necessary to understand the mechanisms which may lead to allow the diffusion through the HVAC systems, which surfaces and filters are usually one of the favourite mechanisms of deposition of the virus. [ 156 , 157 ]. Optimal disinfection systems and modes may be studied to reduce HVAC plant-related risks.…”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out in the Wuhan area (China), Northern Italy, and New York City, experimentally demonstrate that airborne transmission is the dominant route for the spread of the disease and the cause of highest virulence cases [56] . Besides, typical indoor airspeeds, which are generated by mechanical HVAC plants, could allow a 5 μm droplet will travel tens of meters [ 57 , 58 ], which is much greater than the scale of a standard room if emitted from a height of nearly 1.5 m to the floor.…”
Section: Sars-cov-2 Airborne Spreadmentioning
confidence: 99%
“…Experimental studies in a laboratory−controlled environment demonstrated that aerosolized SARS−CoV−2 particles (<5 µm) remained suspended in the air for at least 3 hours, viable in air for at least 1 hour, and on surfaces for up to days. 1 …”
Section: Introductionmentioning
confidence: 99%